Active paper coating based on fish gelatin, palm wax and lemongrass essential oil for ground beef packaging application - Sahid, Nurul Syahida (2020)
In recent years, growing environmental concern regarding the disposal problem of petroleum-based packaging has led to increasing interests towards the use of biopolymers in the food packaging industry. Thus, this study focused on the development of an active paper coating based on natural and biodegradable substances which include fish gelatin (FG), palm wax (PW) and lemongrass essential oil (LEO). The experimental design follows these successive steps: (1) the effects of PW concentration (0-60%) on the physicomechanical and water barrier properties of FG films was determined, (2) different LEO concentrations (0-12%) was incorporated into film coating and its effects on the physicomechanical, water resistance and functional properties of Kraft paper was analysed, and (3) the efficiency of the gelatin/palm wax/lemongrass essential oil (GPL)-coated Kraft paper in maintaining the quality of ground beef during 7 days of storage at 4℃ was evaluated. In the first objective, FG was incorporated with different PW concentrations (0-60%). The gelatin/palm wax (GP) films were significantly (p<0.05) thicker, more opaque, stronger, more flexible and had better resistance towards water and ultraviolet radiation compared to the control film. These characteristics increased significantly (p<0.05) with higher PW concentrations except for the tensile strength which decreased significantly (p<0.05). The results revealed that the GP films incorporated with 15% PW exhibited the best property improvements and was chosen as the film coating on Kraft paper for the second objective. The film coating was incorporated with different concentrations of LEO (0-12%) and the properties of the GPL-coated Kraft paper were evaluated. The GPL film coating significantly (p<0.05) increased the physicomechanical, water barrier and antioxidant properties of the Kraft paper and this effect was more prominent (p<0.05) with higher LEO concentration. However, no antimicrobial property was observed in all paper samples. The GPL-coated Kraft paper incorporated with 12% LEO outperformed the other treatments as an active packaging. Thus, it was used for the following objective in which the effectiveness of the GPL-coated Kraft paper in maintaining the quality of ground beef during 7 days of storage at 4℃ was determined. The properties of the ground beef packed with GPL-coated Kraft paper (GPL/K) were compared to those packed with uncoated Kraft paper (K) and GP-coated Kraft paper without LEO (GP/K). Ground beef that was not packed with any paper packaging was used as control (C). The pH, moisture content and colour properties (L*, a* and b*) of all samples significantly (p<0.05) decreased whereas the total bacterial count, peroxide value and TBARS value significantly (p<0.05) increased with storage time. Nevertheless, compared to the other treatments, the GPL-coated Kraft paper incorporated with 12% LEO was able to significantly (p<0.05) delay all the property changes of the ground beef throughout the 7 days of storage. Thus, the use of GPL-coated Kraft paper could help to effectively maintain the quality of ground beef during chilled storage.